1988
DOI: 10.1042/bj2540781
|View full text |Cite
|
Sign up to set email alerts
|

Mapping and quantification of the major oligosaccharide components of heparin

Abstract: A new method of determining the oligosaccharide composition of commercial glycosaminoglycan heparin is described in which heparin was first depolymerized using heparin lyase (EC 4.2.2.7), and then analysed by a single h.p.l.c. step. All 20 of the porcine and bovine heparins examined were found to contain a small number of major oligosaccharide components, which on average comprised 86% of their mass. The five most abundant oligosaccharides have defined chemical structures. Although the relative abundance of ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
126
1

Year Published

1990
1990
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(133 citation statements)
references
References 21 publications
6
126
1
Order By: Relevance
“…Thus, the RACT-induced F9 cell is similar to the mast cell, which contains a large proportion of molecules with the AT binding property (30%) (2). Structural and biochemical analysis also indicates that the precursor of anticoagulant heparin in mast cells might be present in only small amounts (28,29).…”
Section: Hsmentioning
confidence: 99%
“…Thus, the RACT-induced F9 cell is similar to the mast cell, which contains a large proportion of molecules with the AT binding property (30%) (2). Structural and biochemical analysis also indicates that the precursor of anticoagulant heparin in mast cells might be present in only small amounts (28,29).…”
Section: Hsmentioning
confidence: 99%
“…6) To obtain depolymerized derivatives of the sulfated polysaccharides heparin and fucoidan, chemical methods [7][8][9] and enzymatic reaction systems 10,11) have been used to cleave the glycosidic bonds of the polysaccharides.…”
Section: Effect Of Depolymerization On Anti-hsv-1 Activitymentioning
confidence: 99%
“…Indeed, the available data support this hypothesis (16 -18). As documented by several researchers including ourselves, 3-O-sulfation of glucosamine is a rare modification that constitutes the last step in the biosynthesis of HS (14,15,19,20). We have shown that 3-OST-1 requires an appropriate HS precursor with defined monosaccharide sequence for sulfation to occur and make HS act .…”
mentioning
confidence: 99%